2020
DOI: 10.1111/ajo.13298
|View full text |Cite
|
Sign up to set email alerts
|

What is the anatomical basis of labiaplasty? A review of normative datasets for female genital anatomy

Abstract: Background: Despite increasing numbers of labiaplasties being performed, there is little quantitative information on normal labial diversity to guide medical education, patient education and surgical treatment.Aim: This scoping review will determine what is known in the published literature about the anatomical basis of normal for labia and female genital cosmetic surgery (FCGS). Materials and methods:The scoping review identified ten population-based studies that recorded labial dimensions by searching three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…These non‐significant results can be explained by the small sample size. In their meta‐analysis, Hayes et al 18 concluded that there are sufficient studies on dimensions of labia minora, and it can be added to medical texts so that clinicians understand the physiologic diversity from graduation period only. They concluded that the length of labia majora ranges from 5 to 100 mm, while width ranges from 1 to 60 mm, and these can safely be used as standard.…”
Section: Discussionmentioning
confidence: 99%
“…These non‐significant results can be explained by the small sample size. In their meta‐analysis, Hayes et al 18 concluded that there are sufficient studies on dimensions of labia minora, and it can be added to medical texts so that clinicians understand the physiologic diversity from graduation period only. They concluded that the length of labia majora ranges from 5 to 100 mm, while width ranges from 1 to 60 mm, and these can safely be used as standard.…”
Section: Discussionmentioning
confidence: 99%
“…The labia minora are comprised of non-hair-bearing keratinized squamous epithelium and have minimal connective tissue deeper than the dermis. A systematic review identified significant variation in labia minora length (5-100 mm) and width (1-60 mm) 19 . The largest included study reported measurements of the labia minora in 657 Caucasian asymptomatic women from 15 to 84 years of age with a mean of 43 mm in length (SD 16 mm) and 14 mm in width (SD 7 mm) 20 .…”
Section: Specific Proceduresmentioning
confidence: 99%
“…A systematic review identified significant variation in labia minora length (5-100 mm) and width (1-60 mm). 19 The largest included study reported measurements of the labia minora in 657 Caucasian asymptomatic women from 15 to 84 years of age with a mean of 43 mm in length (SD 16 mm) and 14 mm in width (SD 7 mm). 20 Additional research is needed to compare these data to other ethnicities.…”
Section: Anatomymentioning
confidence: 99%
“…7,8 Indeed there is no such demarcation, with the systematic review by Hayes and Temple-Smith which is contained in this issue highlighting the wide range of normal anatomical variation and that asymmetry between left and right side is common as is protrusion of the labia minora. 1 The crura of the clitoris is contiguous with the labia minora and a major concern with labiaplasty also discussed in this systematic review is the removal of highly sensitive and well vascularised labial tissue with a potential adverse impact on sexual function and pleasure. As discussed in the recent Australian and New Zealand Journal of Obstetrics and Gynaecology (ANZJOG) editorial, 'Moving from critical clitoridectomy', the female organs involved in sexual pleasure have a long history of being poorly understood and under-researched.…”
mentioning
confidence: 98%
“…A commonly desired outcome is 'The Barbie' vulva where the labia minora are trimmed to the extent of invisibility, with no visible protuberance beyond the labia majora. 1 The procedure can be performed by gynaecologists, cosmetic surgeons, plastic surgeons and urologists with various surgical techniques described including wedge resection and labial trimming. 2 FGCS is to be distinguished from vulvoplasty which may be medically indicated in the management of a range of congenital disorders, vulvovaginal malignancy, inflammatory conditions and following genital trauma including vaginal delivery and female circumcision.…”
mentioning
confidence: 99%